A study on end group characterization of poly(phenacyl methacrylate) polymer produced by free radical polymerization - Coskun, M. Fatih; Demirelli, Kadir; Coskun, Mehmet (Taylor & Francis Inc, 2007)
Free-radical homopolymerization and copolymerization of phenacyl methacrylate (PAMA) with methyl methacrylate (MMA) was done using 2,2'-azobis(isobutyronitrile) (AIBN) as the initiator in 1,4-dioxane at 60 degrees C. H-1-NMR and FT-IR spectroscopy confirmed the existence of OCH2 and CH signals and unsaturated structure and CN stretch at the chain end of low molecular weight poly(phenacyl methacrylate)[poly(PAMA)], respectively. The six-membered ring with both ester and ether at the end group was detected by 1H-NMR. In the poly(PAMA), the end groups formed due to chain transfer reactions were found in large concentrations. The mechanism of the formation of end groups has been presented. The behavior of free radical polymerization of PAMA was compared with that of phenoxycarbonylmethyl methacrylate (PCMMA). The molecular weight distribution of the homo and copolymers was determined using gel permeation chromatography. Thermal properties of the polymers were determined using differential thermal analysis (DTA) and thermogravimetric analysis (TGA).
Keywords: free radical polymerization; end group characterization